Disorder of Sex Development, Mosaic Genetic Disorder 45x, 46xy: A Case Report - Awan Nurtjahyo; Asep Nurul Huda; A. Abadi; Aditiawati; Yulisnawati H; Fadil P (HM Publisher, 2022)
Background. Disorder of sex development (DSD) is a congenital disorder associated with interference in chromosomes, gonads, or sexes anatomically. Individual affected with DSD can be recognized since birth due to external genital ambiguity. Sexual chromosome DSD occurred because sexual chromosome numeric or structural disorder. Mosaic karyotype 45X/46XY is among the rare sexual chromosome DSD with incidence less than 1:15,000 live births. DSD individuals are susceptible to stigmatization. This can cause stress, negative emotion, and social isolation. Therefore, DSD individual management should be done as optimal as possible. Case Presentation: Twelve years old girl complaining a bump arose from anterior side of her genital resembles male genital since 4 years prior to admission without micturition and defecation complains. Patient has not experienced menarche. On external genital examination, we found the normal female external genital such as mons pubis, pubic hair, labia majora, labia minora, hymen, perineum, but without clitoris which in this case it is replaced by a glans of penis, arising from anterior commissure of labia majora area, with an urethral estuary. Before the management is done, patient underwent multidiscipline consultations and further examinations. Subsequently, it was approved that the joint conference formation consisting obstetric and gynecology, urologist, and pediatric endocrinologist to determine the optimal management for the patient. Conclusion: In this case, diagnosis was made with history taking, clinical examination, and supporting investigation such as ultrasound imaging and could be followed by biochemistry test, voiding cystourethrography or genitogram to determine next management. Counseling should be done in detail towards the family to know what action is best for the patient. Multidiscipline team was required to get the optimum result either in medical, ethical, or religious point of view. Surgery in this case was considered followed by long term therapy afterwards.